Viral kinetics in untreated versus treated acute HIV infection in prospective cohort studies in Thailand. Issue 1 (26th June 2017) - Ananworanich, Jintanat; Eller, Leigh Anne; Pinyakorn, Suteeraporn; Kroon, Eugene; Sriplenchan, Somchai; Fletcher, James LK; Suttichom, Duanghathai; Bryant, Christopher; Trichavaroj, Rapee; Dawson, Peter; Michael, Nelson; Phanuphak, Nittaya; et al.
Abstract: Introduction : The extent of viral replication during acute HIV infection (AHI) influences HIV disease progression. However, information comparing viral load (VL) kinetics with and without antiretroviral therapy (ART) in AHI is limited. The knowledge gained could inform preventive strategies aimed at reducing VL during AHI and therapeutic strategies to alter the viral kinetics that may enhance the likelihood of achieving HIV remission. Methods : The analysis utilized VL data captured during the first year of HIV infection from two studies in Thailand: the RV217 study (untreated AHI, 30 participants and 412 visits) and the RV254 study (treated AHI, 235 participants and 2803 visits). Fiebig stages were I/II (HIV RNA+, HIV IgM−) and Fiebig III/IV (HIV IgM+, Western blot‐/indeterminate). Data were modelled utilizing spline effects within a linear mixed model, with a random intercept and slope to allow for between‐subject variability and adjustment for the differences in variability between studies. The number of knots in the quadratic spline basis functions was determined by comparing models with differing numbers of knots via the Akaike Information Criterion. Models were fit using PROC GLIMMIX in SAS v9.3. Results : At enrolment, there were 24 Fiebig I/II and 6 Fiebig III/IV individuals in the untreated group and 137 Fiebig I/II and 98 Fiebig III/IV individuals in the treated group. Overall, the median age was 27.5 years old, most were male (89%), and CRF01_AE was the most common HIV clade (76%). By day 12 (4 days after ART in RV254), the untreated group had a 2.7‐fold higher predicted mean VL level compared to those treated (predicted log VL 6.19 for RV217 and 5.76 for RV254, p  = 0.05). These differences increased to 135‐fold by day 30 (predicted log VL 4.89 for RV217 and 2.76 for RV254) and 1148‐fold by day 120 (predicted log VL 4.68 for RV217 and 1.63 for RV254) ( p  < 0.0001 for both) until both curves were similarly flat at about day 150 ( p  = 0.17 between days 150 and 160). The VL trajectories were significantly different between Fiebig I/II and Fiebig III/IV participants when comparing the two groups and within the treated group ( p  < 0.001 for both). Conclusions : Initiating ART in AHI dramatically changed the trajectory of VL very early in the course of infection that could have implications for reducing transmission potential and enhancing responses to future HIV remission strategies. There is an urgency of initiating ART when acute infection is identified. New and inexpensive strategies to engage and test individuals at high risk for HIV as well as immediate treatment access will be needed to improve the treatment of acute infection globally. Clinical Trial Number : NCT00796146 and NCT00796263